STATISTICAL LITERACY OF SECONDARY SCHOOL STUDENTS IN SOLVING CONTEXTUAL PROBLEMS TAKING INTO ACCOUNT THE INITIAL STATISTICAL ABILITY - Risqi, Erlyanna Nur; Rini Setianingsih (Program Studi Pendidikan Matematika Universitas PGRI Kanjuruhan Malang, 2021)
Statistical literacy is strongly needed in the 21st century in reading data information, thinking critically and making decisions. The purpose of this study is to describe the statistical literacy abilities of high school students in solving contextual problems taking into account their initial statistical abilities, with the following indicators, Tier 1 (reading & explaining data), Tier 2 (analyzing, interpreting, interpreting critically, and making conclusions), Tier 3 (presenting data and predicting something). This research is a qualitative in nature, using statistical ability test, statistical literacy test, and interview guidelines to collect data. The subjects of this study consist of three female students of grade XII Senior High School, with high, medium and low initial statistical ability categories. The results of this study revealed that (1) The student with high initial statistical abilities can meet the indicators of Tier 1, Tier 2, Tier 3, so that she can be categorized at level 5 to 6 (critical-mathematics critical), (2) The student with medium ability can fulfil the Tier 1 indicator not fulfil the indicators in Tier 2 and Tier 3, so that it can be categorized at level 3 to 5 (Consistent noncritical-Critical), and (3) The students with low abilities can fulfill the indicators of Tier 1 not fulfil the indicators in Tier 2 and Tier 3, so that it can be categorized at level 1 to 3 (Idiosyncratic-Consistent Noncritical). Therefore, it is important for students and teachers to know statistical literacy skills in order to increase their understanding and ability to understand information in making decisions regarding daily problems.